ECOLOGICAL CLASSIFICATION OF BEECH WOODLANDS IN THE CENTRAL APENNINE THROUGH FREQUENCY DISTRIBUTION OF ELLENBERG INDICATORS - CROSTI, R.; DE NICOLA, C.; FANELLI, G.; TESTI, A. (Annali di Botanica, 2010)
Habitats are often described using a phytosociological approach, meaning that plant communities are classified through a floristic data set. As this approach is based exclusively on a floristic assemblage analysis, much of the ecological information about the species may be lost. For this reason, Ellenberg indicators (EIV) are used to incorporate the information provided by vegetation relevés; for each species, the EIVs express the ecological requirements for seven main environmental factors. Based on that assumption, this study focuses on the use of EIVs in detecting discriminants in a homogeneous habitat (via similarity-dissimilarity tests for each Ellenberg indicator). This helps to identify the key ecological factors structuring the vegetation. The study area is located in the Upper Sangro Valley in the central Apennines (Abruzzo region) where 94 phytosociological relevés and pedological profiles were carried out in beech and mixed woodlands. Based on a flora set, the Cluster Analysis divided the vegetation relevés into seven groups which are floristically distinguished. For each of the groups, the frequency distribution of the single EIV of all the recorded species in each relevé was compared through a non-parametric test which delivered the probability of two distributions being the same. Combining the results of the two different analyses we were able to rearrange the outcome of the cluster analysis into an ecological classification, which was then confirmed by field data on soil parameters.